Spatial Variations and Potential Risks of Heavy Metals in Seawater, Sediments, and Living Organisms in Jiuzhen Bay, China - Xia Sun; Bao-Shi Li; Xuan-Li Liu; Cheng-Xuan Li (Journal of Chemistry)
Coastal waters are polluted by heavy metals to varying degrees, posing potential risks to marine ecology and human health. In May 2006, the pollution levels, sources, and ecological risks of heavy metals (Cu, Pb, Zn, Cd, Hg, and As) in seawater, surface sediments, and living organisms were studied in Jiuzhen Bay in Fujian, China. This study identified Hg (0.26–0.72 µg/L) and As (20.3–31.5 µg/L) pollution in the seawater of Jiuzhen Bay. In sediments, heavy Pb pollution (946 µg/g dw) was only detected at one station at a level posing very serious potential risk, while Hg pollution (0.052–0.087 µg/g dw) was observed at three stations at a level posing serious potential risk. No heavy metal pollution was detected in sediments at other stations. The concentrations of five heavy metals (Cu, Zn, As, Cd, and Pb) exceeded the corresponding National Quality Standards for oysters, indicating heavy pollution, based on an ecological risk assessment. In clams, two heavy metals (Pb and As) exceeded the standards, indicating light pollution, based on an ecological risk assessment. No heavy metal pollution was found in fish or shrimps. The heavy metals in the seawater and sediments of Jiuzhen Bay are mainly derived from the river discharges of Luxi and Wujiang Rivers although sewage discharge along the coast of Jiuzhen Bay is another source of heavy metal pollution at some stations. Given the pollution of Pb, Hg, and As in seawater and sediments at some stations within the bay, the potential risks of Pb, Hg, and As in living organisms to both the marine ecology and human health deserve increased attention.